4a. Chain of Portable Health Folders - Mateus, D.; Martins, A.; Correia, R. (eHealth 2024, 2024)
Introduction: After their earliest development in the 20th century, Personal Health Records (PHRs), and Over-the-counter (OTC) records, developed around the growing patient needs of availability, empowerment, and patient-centric data management. By, leveraging modern technologies and supporting a personalized approach to healthcare [1], Health Wallets represent the next step in the fast evolution of digital health records, hence the paper’s objective at exploring the characteristics of existing patient information platforms, advantages and limitations of their use, and gaps in the current solutions. Material and Methods: To reach the research objective, a Systematic Literature Review following the PRISMA framework will be conducted [2]. 3 databases were used: IEEE Xplore, Scopus, and PubMed – chosen for their coverage in the fields of management, healthcare and technology. Grey literature results were considered due to the novelty of the topic. There were no restrictions to the years of analysis. The initial search, following 5 distinct keywords (“Health Wallet”, “Digital Health Wallet”, “Personal Health Wallet”, “Healthcare Wallet”, “Medical Wallet”). 850 papers were identified, from which 36 articles were kept. Results: Results show that healthcare professionals generally welcome the introduction of Apps and Wallets in their practices [3]. Although the concept was first explored in 2017, comprehensive research accelerated with the Covid-19 pandemic, in 2021. Patient information platforms, used by both medical professionals and patients, are characterized by being portable health record management systems, similar to folders but that allow for information transactions. The main reported concerns relate to Interoperability issues, Data Protection, and Quality of Care. Conversely, the main advantages usually lie on Data Aggregation, Accessibility, and Care continuity. Continuous use of these systems is influenced by factors such as user attitude, satisfaction, perceived usefulness, and self-efficacy [4]. Discussion: Physicians may feel reluctant to deviate from routines [5] with the major issues identified effectively addressed through the usage of FHIR, Blockchain and Role Based Access, as well as Bidirectional Communication and Mutual Authentication. However, semantic challenges may still affect interoperability. These should aim to mitigate information dissemination for Physicians, i.e., concentrating information, joining different sources into one without the need for manual handling. They should integrate seamlessly into existing processes to avoid adding complexity to workflows. Future research should dwell on the diminishing marginal returns of another tool. One of the contributions of this paper, is that the ideal Health Wallet should guarantee confidentiality and privacy, builds on user experience throughout the service, and increases physicians efficiency and effectiveness; targeting time, resource and information management. Ongoing developments are promising, with tools such as the BioWallet, with the potential to bridge these existing gaps. This work was supported by the project “BLOCKCHAIN.PT (RE-C05-i01.01—Agendas/Alianças Mobilizadoras para a Reindustrialização, Plano de Recuperação e Resiliência de Portugal na sua componente 5—Capitalização e Inovação Empresarial e com o Regulamento do Sistema de Incentivos “Agendas para a Inovação Empresarial”, aprovado pela Portaria N.° 43-A/2022 de 19.01.2022).